Temporal Progression of Retinal Progenitor Cell Identity: Implications in Cell Replacement Therapies - Javed, Awais; Cayouette, Michel (Frontiers in Neural Circuits, 2017)
Retinal degenerative diseases, which lead to the death of rod and cone photoreceptor cells, are the leading cause of inherited vision loss worldwide. Induced pluripotent or embryonic stem cells (iPSCs/ESCs) have been proposed as a possible source of new photoreceptors to restore vision in these conditions. The proof of concept studies carried out in mouse models of retinal degeneration over the past decade have highlighted several limitations for cell replacement in the retina, such as the low efficiency of cone photoreceptor production from stem cell cultures and the poor integration of grafted cells in the host retina. Current protocols to generate photoreceptors from stem cells are largely based on the use of extracellular factors. Although these factors are essential to induce the retinal progenitor cell (RPC) fate from iPSCs/ESCs, developmental studies have shown that RPCs alter fate output as a function of time (i.e. their temporal identity) to generate the seven major classes of retinal cell types, rather than spatial position. Surprisingly, current stem cell differentiation protocols largely ignore the intrinsic temporal identity of dividing RPCs, which we argue likely explains the low efficiency of cone production in such cultures. In this article, we briefly review the mechanisms regulating temporal identity in RPCs and discuss how they could be exploited to improve cone photoreceptor production for cell replacement therapies.